KUALITAS GELATIN KULIT KAKI AYAM RAS PEDAGING DENGAN LAMA PERENDAMAN DAN KONSENTRASI NaOH YANG BERBEDA (Quality of skin food Gelatin Broiler with different Curing and NaOH Consentration) - Hasma Hasma (Jurnal Ilmu dan Teknologi Peternakan, 2018)
This study aims to obtain the quality of broiler skin food gelatin that gets the old treatment of immersion and concentration different NaOH. This research was compiled by Randomized Complete Random Factor (RAL) 3 x 3 factorial design. Factor 1 was curing period (8, 16 and 24 h, respectively) and factor 2 was NaOH concentration level (1, 2 and 3%, respectively). Each unit of the experiment uses 200 grams of broiler skin foot (shank). The instruments used were analytical scales, beaker, tracing paper, scissors, cutter, plastic container for soaking, water bath, Erlenmeyer, stirrer, thermometer, sieve, oven, crusher, mold, pH meter, and texture analyzer. The variables observed in the experiment were the yield, acidity (pH) and gel strength. The results showed the highest average of gelatin content at 2% NaOH concentration of 15.71%. The degree of acidity (pH) shows that the longer the immersion time (24 hours) and the higher the NaOH concentration (3%) the higher the resulting pH. The strength of the gel (gram bloom) showed that the 1% NaOH concentration that formed the gel at 24 hours of immersion was 178.15 grams bloom.